Response-category conflict improves target memory in a flanker paradigm. Issue 3 (16th March 2022) - Muhmenthaler, Michèle C.; Meier, Beat
ABSTRACT: Previous studies have shown that cognitive control demands and long-term memory interact in several ways. For example, trial-unique Stroop entities which consist of two perceptually distinct stimulus dimensions can enhance subsequent memory. In the present study, we investigated whether this effect generalises to a flanker paradigm. In the study phase, 60 participants had to classify target pictures which were flanked by pictures that were either congruent or incongruent to the target with regard to the response categories, thus manipulating response-category conflict. Then we assessed recognition memory. The results showed that the response-category conflict enhanced subsequent memory for incongruent targets, implying an up-regulation of top-down control that fostered memory encoding. The results demonstrate that the beneficial memory effect of a response-category conflict generalises to a flanker task.